Prevalence of colistin resistance in clinical isolates of Pseudomonas aeruginosa: a systematic review and meta-analysis - Narimisa, Negar; Keshtkar, Abbasali; Dadgar-Zankbar, Leila; Bostanghadiri, Narjess; Far, Yasaman Rouein; Shahroodian, Soheila; Zahedi Bialvaei, Abed; Razavi, Shabnam (Frontiers in Microbiology, 2024)
Objective: The emergence of resistance to colistin, the last resort for treating severe infections caused by Pseudomonas aeruginosa, poses a significant threat to public health. This meta-analysis aimed to investigate the prevalence of colistin resistance in clinical isolates of P. aeruginosa.A comprehensive search of MEDLINE (PubMed), Web of Science, and Scopus databases was conducted to identify relevant articles published until December 2023.Subsequently, a meta-analysis was performed using Stata software to examine the pooled prevalence of colistin resistance and to conduct subgroup analyses.Results: A total of 619 studies were included in the meta-analysis, revealing a global prevalence of colistin resistance of 1% among all P. aeruginosa isolates. Furthermore, cystic fibrosis patients exhibited the highest resistance to colistin, with a prevalence of 7% among the examined diseases.The increase in colistin resistance in P. aeruginosa in recent years from 2% (in the period of 2006-2010) to 5% (in the period of 2020-2023) underscores the need for implementing infection prevention programs, using appropriate treatment regimens, and disseminating comprehensive information on antimicrobial resistance patterns. These measures are crucial for addressing this growing public health concern.